THE EDUCATION OF ROMA IN GREECE - Vergidis, Dimitris k (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
In this paper we examine schooling as a factor in the social integration of the Roma who are Greek citizens. It refers to the living conditions of the Greek Roma and the transformation which their social organization is undergoing, taking their economic activities as a starting point. In order to tackle the educational exclusion of the Roma, two different educational policies have taken shape. There is the official educational policy which argues that the educational exclusion of the Roma should be dealt with through positive discrimination so that the romani children can be integrated into regular schools. On the other hand, out of criticism of the role of the school in the reproduction of social inequalities, springs the demand for a different educational policy which would adapt schooling to the culture of the Roma and respond to their particular needs.